Meeting the infrastructure challenge in Latin America and the Caribbean - World Bank (Directions in Development - General, 1995)
The countries of Latin America and the Caribbean (LAC) stand at a point of transition. During the 1980s in the face of the unavoidable need to correct macroeconomic imbalances, economic growth largely came to a halt, some of the poor became poorer, and not only new investment but even routine maintenance of economic infrastructure was often neglected or deferred. This report suggests a number of ideas to help countries address their infrastructure challenges, including a variety of models for structuring the participation of domestic and international private capital. The report also states the World Bank's commitment to serve as a proactive catalyst for mobilizing private capital for improved infrastructure service provision in LAC. The World Bank will intensify efforts toward policy and regulatory reform and contribute financial resouces or provide guarantees to help strenghten infrastructurae in LAC